KARAKTERISTIK BUDAYA KOMUNITAS ISLAM PEGAYAMANBULELENG, BALI - Budarsa, Gede (Humanis; Volume 11. No 1. April 2015, 2015)
Ethnicity in Bali is not dominated by Hinduism. Pegayaman is a kind of Islam community that lived in Bali. Interaction with Balinese culture made them used Balinese culture in their life. In this research was founded that Islam Pegayaman community was formed on Buleleng Kingdom. They were formed by three ethnic such as Javanese ethnic from Mataram Kingdom, Balinese ethnic (Balinese girl) and Bugis from North Sulawesi . The cultural characteristic of Islam Pegayaman community is dominated by Balinese culture like Balinese language, subak system, sekaa, Balinese culinary, Balinese named system and so on.
Keywords: Islam Community, Balinese Culture, Ethnic